BETWEEN SHARIA ARBITRATION AND RELIGIOUS COURTS: JURISDICTIONAL CONFLICT AND JUDICIAL CONSIDERATIONS ON ARBITRATION CLAUSES IN SUPREME COURT DECISIONS - Muhammad Fakhril Umam; Dhika Tabrozi; Roisul Umam Arrasyidi; Wijdan Hibatulloh al-Wafa (Universitas Islam Indonesia, 2026)
Purpose - This study aims to analyze the conflict of jurisdiction between the National Sharia Arbitration Board (Basyarnas) and the Religious Courts in the resolution of sharia economic disputes, particularly regarding the effectiveness of arbitration clauses when such institutions are not structurally available in certain regions. The focus of the study is directed at the judges’ legal considerations in Supreme Court Decisions No. 159 K/Ag/2021 and No. 175 K/Ag/2021. Methods - The research employs a normative legal method using a statutory and case study approach, focusing on Supreme Court Decisions No. 159 K/Ag/2021 and No. 175 K/Ag/2021. The analysis utilizes Friedman’s legal system theory and Radbruch’s legal objectives to examine the rationality of the judges’ considerations. Findings - The results of this study found that the structural absence of Basyarnas in a region constitutes the primary ratio decidendi for judges to assume adjudicatory authority. Within Friedman’s framework, there is an interaction between the limitations of the legal structure and a responsive legal culture, which prompts judges to engage in legal discovery through the interpretation of Article 1344 of the Civil Code. Based on Radbruch’s conceptual framework, the judge’s legal balancing, in its implications, incorporates legal objectives within a framework aimed at achieving substantive justice for the aggrieved party; the utility-oriented nature of the decision provides practical benefits for the disputing parties; and certainty ensures that regulations are clearly formulated and not open to multiple interpretations, thereby providing legal certainty for the litigants as subjects of law. Research contribution/limitations - This study is limited to a normative analysis of specific cases; therefore, generalizations are limited. Originality/value - This study demonstrates that under conditions of institutional limitations, judges tend to prioritize substantive justice and the effectiveness of dispute resolution over formal legal certainty